Types of Catalysts in Oil Refining - Asadova Dilnavoz Fayzullaevna (Zien Journals, 2022)
This article is devoted to summarizing information about the current state and development trends of the catalytic cracking process. The main directions of using the process in the world are studied: obtaining high-octane gasoline, hydrocarbon gases, diesel fuel. In the course of the generalization, the possibilities of involving polymeric waste and biofuel production waste in raw materials were considered, helping to solve the problem of their disposal. The state of the process catalysts and their development trends were studied: a decrease in the content of rare earth metals and an increase in the content of iron. Mention is made of methods of preparation of raw materials that improve the performance of the process.
Keywords: Catalysts; inhibitor; refinery industry; catalytic process